Conversion in American Philosophy : Exploring the Practice of Transformation - Ward, Roger A.; Project Muse. (New York : Fordham University Press, 2004)
Annotation In this fresh, provocative account of the American philosophical tradition, Roger Ward explores the work of key thinkers through an innovative and counterintuitive lens: religious conversion. From Jonathan Edwards to Cornel West, Ward threads the history of American thought into an extended, multivalent encounter with the religious experience. Looking at Dewey, James, Peirce, Rorty, Corrington, and other thinkers, Ward demonstrates that religious themes have deeply influenced the development of American philosophy. This innovative reading of the American philosophical tradition will be welcomed not only by philosophers, but also by historians and other students of America's religious, intellectual, and cultural legacy.
Introduction: Conversion and the practice of transformation -- The philosophical structure of Jonathan Edwards's religious affections -- Habit, habit change, and conversion in C.S. Peirce -- Reconstructing faith : religious overcoming in Dewey's pragmatism -- Transforming obligation in William James -- Dwelling in absence: the reflective origin of conversion -- Creative transformation : the work of conversion -- The evasion of conversion in recent American philosophy.
English.
Description based on print version record.
Keywords: Philosophy; Philosophy & Religion; Philosophy, American; Philosophie americaine -- Histoire; Philosophy, American -- History; History; Electronic books